Additional calcium carbonate into concentrate diet for sheep fed ensiled king grass as a based-diet - I-W Mathius; D Lubis; E Wina; D.P Nurhayati; I.G.M Budiarsana (Indonesian Center for Animal Research and Development (ICARD), 1997)
In order to ascertain the effect of additional calcium carbonate into concentrate diet, on the performance of sheep fed ensiled king grass as a basal diet, a trial was conducted using 28 growing sheep ( average body weight 17 _+ 1 .4 kg). Based on body weight, the animals were grouped and randomized into four dietary treatments in block randomized design . Dietary treatments were (i) chopped king grass + 400 g of concentrate, (ii) ensiled king grass + 400 g concentrate + 0 % of calcium carbonate, (iii) ensiled king grass + 400 g concentrate + 5 % calcium carbonate and (iv) ensiled king grass + 400 g concentrate + 10 % calcium carbonate . Results showed that offering 5 % of calcium carbonate into concentrate diet increased (P < 0 .05) dry matter and nutrient intake of silage, but digestibility coefficients were similar (P > 0 .05) for all groups . No differences in the apparent digestibility of the nutrient components were observed, but crude protein decreased significantly (P < 0 .05) . A significant relationship ( P < 0 .01) was found between nitrogen intake (NI) and nitrogen retention (NR), and the equation was NR = - 0.1848 + 0.3788 NI ( r = 0.9 ) . Based on data found that feeding only ensiled king grass as a single diet could not meet the maintenance requirement of energy and protein, therefore, additional energy and crude protein sources is needed . Keywords : Silage, king grass, growing sheep